A Study on Pattern of Heart Disease and Maternal and Fetal Outcome of Pregnancy in a Tertiary Level Hospital - Akhtar, Nahreen; Sultana, Tajmira; Sayeeda, Syeda; Parveen, Tabassum; Begum, Firoza (University Heart Journal, 2016)
Background: Cardiac disease is the most common cause of indirect maternal deaths and the most common cause of death overall. It complicates 1% of maternal death. Objective: Management of pregnancy in patients with valvular heart disease continues to pose a challenge to the clinician.the present study was therefore design to find the pattern of Heart Disease and to evaluate the maternal and fetal outcome of pregnancy. Method: This is a cross sectional study done during the period Jan to Dec, 2011in fetomaternal medicine wing of department of Obs & Gynae, BSMMU. All the patients admitted with heart disease in pregnancy during this study period were included in this study. This study prospectively enrolled 54 pregnant women with heart disease.All cases were followed during pregnancy , labour, delivery and in early puerperium. Results: The mean (SD±) age of the patients was 26.08 ± 3.96 ranging from 20 to 35yrs, most ( 26% ) belonged to age group 26 - 30yrs and five (9.26% ) belonged to >30years of age group. Most of the patients 21 (38.89%) were primigravid and 16(29.63%) patients were of second gravida. Out of 54 patients 41(75.93%) women received regular antenatal checkup.Thirty eight(70.37%) patients suffered from rheumatic heart disease. Twenty patients had single valvular involvement, either mitral, tricuspid or pulmonary valve with or without complication. Most of the patients had EF >50% and two patients had EF <49%. Two patients had mild mitral stenosis( >1.5cm2), 5 patients had moderate mitral stenosis (1-1.5cm2) and 6 patients had severe mitral stenosis (<1cm2). Conclusion: Patients with heart disease should be meticulously managed preconceptionally up to the postpartum period by maternal-fetal medicine specialists, obstetricians, cardiologists, and anesthesiologists using a multi-disciplinary approach to their cardiac conditions to have a better outcome of mother and baby. University Heart Journal Vol. 11, No. 1, January 2015; 36-41